Uso de glicerina na ensilagem de milho ou no concentrado para terminação de cordeiros - Oliveira, Tatiane Martins de (2014)
This study was performed to evaluate the effects of adding semi-purified glycerin in ensiling of corn, to analyze the chemical composition, digestibility, conservation quality, in situ degradability and also to assess the effects of glycerin in finishing rations of lambs. For this, three experiments with completely randomized design were performed. In the first experiment, glycerin doses: 0, 5, 10, 15 and 20% (natural matter basis) added silage corn, vacuum packed (850 g), sealed with wrapping model TeqMaq TM 280 and opening 120 days. Total dry matter losses in storage and aerobic stability and chemical composition of silage were evaluated. In aerobic stability of silage pH and temperature were collected every 24 hours, the period 0-192 hours after silo opening. The results were analyzed by regression analysis (P <0.05). Corn silage with no added glycerin showed higher DM losses (10.17%) during storage. The lowest concentration of DM (271.6 g kg-1 NM), MM (37.4 g kg-1 DM), NFC (188.6 g kg-1 DM) and TDN (638.8 g kg-1 DM ) were determined on silage corn with no added glycerin, with the quadratic effect of (P <0.05). The corn silage with added 15% and 20% glycerin, showed higher TC of 891.1 and 897.8 g kg-1 DM, respectively. These silages showed the greater aerobic stability and lower total dry matter losses. In the second experiment, corn silage was used, without added glycerin, 4% and 9% glycerin (natural matter basis) which is the chemical composition of silage, in vitro digestibility of dry matter (DM) on an artificial incubator TE-150 (Tecnal ). Aerobic stability (0-216 hours) after opening the silos, every 24 hours, in situ degradability of dry matter (DM) and the disappearance of neutral detergent fiber (NDF) in samples incubated for times 0, 3, 6, 12, 24, 36, 48, 72 and 96 hours in three fistulated cattle. Statistical analyzes were performed by Bayesian inference and analysis of variance (p <0.05). The addition of glycerin in 4 or 9% increased concentrations of DM and TDN. No changes in the amounts of mineral matter, crude protein, ether extract, lignin, NDF, TC, NFC and IVDDM were observed. In potential DM, degradation was increased in the soluble fraction (a) and reduction in the potentially degradable fraction (b). The effective degradability (ED) of DM and NDF were higher in silages with added glycerin. The aerobic stability of silage with glycerin had lower pH and maximum temperature. In the third experiment 4.4 and 8.8% glycerin was provided on dry matter (DM) to the rations of lambs, with added maize silage or concentrate. Twenty-eight lambs, Dorper x Santa Ines, males (20 ± 1.8 kg BW) were evaluated for dry matter intake (DMI), average daily gain (ADG), body weight at slaughter (BWS), hot carcass weight (HCW) and cold carcass weight (CCW) and their income. The chemical composition and total digestible nutrients (TDN) of silage cornwith added and no added glycerin was determined. The apparent digestibility of DM, crude protein (CP), ether extract (EE) and neutral detergent fiber (NDF) was determined by feces collected and determination of indigestible dry matter (IDM) as an internal marker. The addition of glycerin increased the DM concentration of 289.6 g kg-1 DM to 323.7 and 339.9 g kg-1 DM; and the TDN of 547.0 g kg-1 DM to 576.1 and 626.9 g kg-1 DM in silage corn. In assessing the digestibility coefficients, glycerin added to the concentrate resulted in higher DM digestibility (78.85 and 82.56%), CP (70.19 and 79.07%) and EE (77.49 and 83.15%) of rations. There was an average 7.4% increase in DMI and 10.5% in NDF intake by lambs when glycerin was added to the concentrate. Also, ADG (200 and 210g) was higher with the addition of 4.4 and 8.8% glycerin, respectively, to the concentrate. There was no effect with dose and form of glycerin added to feed (silage or concentrate) in body weight at slaughter, weights of hot and cold carcass and the carcass. Thus, the results show that the addition of glycerin in silage corn enabled a richer nutritional value. There was higher ruminal degradability, reduced dry matter losses and increased aerobic stability of silages. In lamb finishing, glycerin must be added to the concentrate, thus providing greater dry matter intake and average daily gain of finishing lambs, and on a larger scale production, can provide higher profitability per kilogram of carcass to increase productivity in the same confinement time.